A measurable assessment of the connections between surface- and ground-water in redoes plateau, china’s hailiutu river basin - ZHANG XIAO, ZHANG XIAO; DR MOHAMMED SALEH NUSARI, DR MOHAMMED SALEH NUSARI; DR. AIMAN AL-ODAINI, DR. AIMAN AL-ODAINI (International Journal of Multidisciplinary Research and Studies, 2024)
As for the Erdos Plateau, its "Since surface water and groundwater are so intricately connected, hydrological processes are notoriously difficult to understand. The more we learn about hydrology, the better we can manage the water sources that are accessible at the same time. Long-term economic growth and poverty reduction depend on a thriving ecosystem and the responsible use of water supplies. There haven't been many studies done here to determine if groundwater withdrawal affects stream flow, and that's likely because of how intricate the water systems here are. To maintain the long-term viability of water resources management, a deeper understanding of the interconnections between groundwater and surface water is required. This study seeks to further our understanding of the groundwater-surface water exchange occurring on Erdos Plateau "with regards to how the Erdos Plateau's groundwater and surface water interact with one another.